2017
DOI: 10.1111/1462-2920.13692
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of the human gut microbiome from urbanized and pre‐agricultural populations

Abstract: Summary Metagenomic studies of the human gut microbiome have only recently begun to explore the differences in taxonomic composition between subjects from diverse geographical origins. Here, we compared taxonomy, resistome and functional metabolic properties of publicly available shotgun datasets of human fecal samples collected from different geographical regions (Europe, North America, Asia and Oceania). Such datasets encompassed gut microbiota information corresponding to 13 developed/industrialized societi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
119
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(147 citation statements)
references
References 45 publications
23
119
2
3
Order By: Relevance
“…Previous reports have compared the gut microbiota of individuals in non-industrialized societies with those with a westernized lifestyle, such as comparing gut microbiota of Europeans and with to that of children in Burkina Faso 12 , children and adults in Malawi and Amazonian Americans 13 , adult Hadza hunter-gatherers in Tanzania 14 , and adult Papua New Guineans 15 . Differences in the alteration of gut microbiota in the present study compared with the previous reports might be influenced by ethnicity and the levels of urbanization 29,30 .…”
Section: Discussioncontrasting
confidence: 68%
“…Previous reports have compared the gut microbiota of individuals in non-industrialized societies with those with a westernized lifestyle, such as comparing gut microbiota of Europeans and with to that of children in Burkina Faso 12 , children and adults in Malawi and Amazonian Americans 13 , adult Hadza hunter-gatherers in Tanzania 14 , and adult Papua New Guineans 15 . Differences in the alteration of gut microbiota in the present study compared with the previous reports might be influenced by ethnicity and the levels of urbanization 29,30 .…”
Section: Discussioncontrasting
confidence: 68%
“…Studies found U.S. individuals’ gut microbiomes have 15−30% fewer species than contemporary hunter–gatherer individuals’ gut microbiomes . Furthermore, while there is enormous overlap in composition of symbiotic microbes between different industrialized populations, contemporary hunter–gatherer gut microbial compositions were independent both of each other and of the microbiome compositions from industrialized populations . The observation that human gut microbial composition is similar across industrialized populations is consistent with the possibility that symbiotic microbial uniformity could partially account for epidemiological similarity across otherwise disparate world regions.…”
Section: Gut Microbiotasupporting
confidence: 53%
“…These transitions also likely brought about major changes in the composition of symbiotic microbiota, including generally reduced diversity and enhanced pathogenic virulence. Suppositions regarding pre‐Agricultural Revolution gut flora are based on analyses comparing the gut microbial compositions of contemporary people who practice hunting–gathering subsistence strategies in nonindustrialized communities in Tanzania (Hadza), Peru (Matses), Malawi, and Venezuela, and fossil assemblages of Neanderthals (compilation from Spain, Croatia, Germany, and Russia), Denisovans (from Siberia), and other early hominins (from Spain) with those of contemporary industrialized populations in Europe, North America, Asia, and Oceania . We note that contemporary hunter–gatherers offer an imperfect proxy for premodern gut microbiomes …”
Section: Microbial Transitions In Human Historymentioning
confidence: 99%
“…For example, it has been reported that the gut microbiota of children from Burkina Faso were enriched of Bacteroides , while Enterobacteriaceae , pathogenic intestinal microbes causing diarrhoea, were significantly lower compared to Italian children . A meta‐analysis of metagenomic datasets obtained from faecal samples of healthy adults living in 13 different industrialized regions, as well as two preagricultural communities, indicated that the urbanization process has significantly shaped the gut microbiota, thereby potentially impacting the overall functionality of the gut microbiome . Besides, epidemiologic studies have suggested that the incidence of autoimmune disorders is increasing in industrialized countries potentially reflecting environmental/dietary/microbial population changes .…”
Section: The Gut Microbiota Systemmentioning
confidence: 99%